FNA cytology of solitary fibrous tumors and the diagnostic value of STAT6 immunocytochemistry. Issue 1 (15th September 2017) - Tani, Edneia; Wejde, Johan; Åström, Kristina; Wingmo, Inga‐Lill; Larsson, Olle; Haglund, Felix
Abstract : BACKGROUND: Solitary fibrous tumors (SFTs) are rare mesenchymal tumors commonly located in the pleura, soft tissues, or meninges and are characterized by the NGFI‐A‐binding protein 2 ( NAB2 )–signal transducer and activator of transcription 6 ( STAT6 ) fusion gene. Recent studies have indicated that nuclear STAT6 immunohistochemistry is a specific marker for SFTs. METHODS: The authors reviewed fine‐needle aspiration (FNA) specimens from extracranial SFTs diagnosed at their institution between 1993 and 2017. Histologic blocks and available formalin‐fixed smears of FNA specimens from SFTs were investigated for STAT6 immunoreactivity using a monoclonal antibody. STAT6 immunocytochemistry was also investigated in schwannomas and spindle cell lipomas. Cytopathologic and clinical characteristics were described. RESULTS: Nineteen benign and 9 malignant SFTs were identified. Both benign and malignant SFTs had a female predominance (female‐to‐male ratio, 2.8:1 and 1.25, respectively). Localization varied, and approximately one‐half of the extrapleural tumors were located in the extremities and frequently were intramuscular. Benign and malignant primary tumors had limited differences in cytologic presentation, the most notable feature being nuclear pleomorphism. Cytomorphologic features included low‐to‐moderate cellularity of mixed oval, elongated, round, and stellate cells with pink collagenous stroma and hypercellular clusters with infrequent atypia. In metastatic SFTs, the cytopathology was suggestive of sarcoma. Immunohistochemistry revealed nuclear STAT6 immunoreactivity in SFTs (n = 5) with cytoplasmic reactivity in cytologic mimickers. CONCLUSIONS: Benign and malignant SFTs have common cytopathologic features, and the ability to distinguish between them is limited. Nuclear STAT6 immunoreactivity is a valuable cytologic marker for SFTs. Cancer Cytopathol 2018;126:36‐43. © 2017 American Cancer Society. Abstract : Descriptive cytopathology and clinical presentation are investigated in 19 benign and 8 malignant solitary fibrous tumors. Immunocytochemistry for signal transducer and activator of transcription 6 (STAT6) is valuable in the fine‐needle aspiration diagnosis of solitary fibrous tumor.